2014
DOI: 10.1186/1475-2840-13-64
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in LDL-induced cardiovascular damage and the protective role of estrogens against electronegative LDL

Abstract: BackgroundIncreased levels of the most electronegative type of LDL, L5, have been observed in the plasma of patients with metabolic syndrome (MetS) and ST-segment elevation myocardial infarction and can induce endothelial dysfunction. Because men have a higher predisposition to developing coronary artery disease than do premenopausal women, we hypothesized that LDL electronegativity is increased in men and promotes endothelial damage.MethodsL5 levels were compared between middle-aged men and age-matched, preme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
3
9
0
Order By: Relevance
“… 52 , 53 Elevated levels of L5 were observed in the plasma of patients with metabolic syndrome, a group of metabolic abnormalities that are associated with CVDs, which is used to identify individuals with high cardiovascular risk. 89 Together these results suggest that LDL electronegativity might be considered as a novel predictor of cardiovascular risk.…”
Section: Clinical Importance Of the Ldl Electronegativity Index In Prmentioning
confidence: 84%
“… 52 , 53 Elevated levels of L5 were observed in the plasma of patients with metabolic syndrome, a group of metabolic abnormalities that are associated with CVDs, which is used to identify individuals with high cardiovascular risk. 89 Together these results suggest that LDL electronegativity might be considered as a novel predictor of cardiovascular risk.…”
Section: Clinical Importance Of the Ldl Electronegativity Index In Prmentioning
confidence: 84%
“…Hormonal and genetic parameters were not monitored in our study; however, previous scientific evidence has confirmed that both parameters influence lipid metabolism and LDL modifications (oxidative or not) 31 . According to Lee et al, during puberty, increased estrogen levels prevent the oxidative DNA damage and endothelial senescence induced by LDL(-) 32 . Our study was not able to confirm that finding; however, more than 94% of adolescents were in the pubertal stage, and both groups showed similar distributions between girls and boys.…”
Section: Discussionmentioning
confidence: 99%
“…LDL becomes more atherogenic and toxic as its particle size decreases and its electronegativity increases [ 42 ]. A recent study found that LDL electronegativity is higher in male patients with metabolic syndrome (MetS) than female patients with MetS, which underlie the increased propensity to CAD observed in male patients [ 43 ]. Previous study showed that increased sdLDL fraction and decreased LDL particle size were positively correlated with the extent and severity of CAD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%